Development and Validation of a TPACK Instrument for Preservice Teachers in the Faculty of Engineering UNY - Destiana, Bonita; Priyanto, Priyanto; Walipranoto, Ponco; Irfan, Rahmatul (Elinvo (Electronics, Informatics, and Vocational Education), 2021)
It is crucial to assess teachers' competency using TPACK. Therefore, the objective of this study was to develop a TPACK instrument for preservice teachers in the Faculty of Engineering, Universitas Negeri Yogyakarta. This study designed the TPACK instrument through 4 stages, namely: (1) literature study to determine the construct and statement items, (2) expert judgment to meet content validity, (3) revision and refinement of items from the review results, (4 ) validity and reliability testing. The research sample consisted of 200 preservice teachers. Validity and reliability testing used Confirmatory Factor Analysis (CFA) with a SmartPLS software program. The results suggested that the instrument met convergent validity with a loading factor value > 0.4, which ranged from 0.802 to 0.932, and discriminant validity, which indicated that the factor loading value for each observed variable with each latent variable was higher than the factor loading value with other latent variables. Composite Reliability values ranged from 0.908 to 0.954, and Cronbach Alpha ranged from 0.867 to 0.936, indicating that the instrument was reliable. Thus this instrument was considered effective in measuring the TPACK of preservice teachers preparing to be productive teachers in vocational high schools.